Influence of Geometric Parameters of the Landing Gear on the Center of Gravity of the Aircraft - Aghayev, E.A. (Herald of Azerbaijan Engineering Academy, 2023)
The article examines the influence of geometric parameters of landing gear on the center of gravity of the aircraft. It is found that the geometric parameters of the landing gear directly affect the displacement of the center of gravity of the aircraft. A mathematical relationship is established between the weight and center of gravity of the aircraft. The influence of changes in the geometric parameters of the landing gear on the center of gravity and weight of the aircraft is shown in the MATLAB Simulink software package.